Gambaran Perilaku Kebersihan Diri Saat Menstruasi Pada Siswi Kelas VIII SMP Negeri 13 Kupang Tahun 2019 - Ramly, Ifna Qwinid; Ndoen, Honey Ivon; Ndoen, Enjelita M. (Timorese Journal of Public Health, 2020)
Personal hygiene during menstruation is an action to maintain health and hygiene in female genital areas during menstruation. Based on data compiled from the Central Statistics Agency and the National Development Planning Agency in 2010, 63 million female adolescents in Indonesia paid less attention to the hygiene of their reproductive organs when menstruating. Furthermore, infectious disease incidence that occurred in adolescents’ reproductive tract (10-18 years) was about 42%. This research purposed to describe personal hygiene behavior during menstruation in female students of class VIII SMPN 13 Kupang. The research was a descriptive study with a quantitative approach. The number of samples was 63 female students of class VIII SMPN 13 Kupang taken by the simple random sampling technique. The results showed that the majority of respondents had a good level of knowledge (85,71%) and a positive attitude (80,95%) towards personal hygiene behavior during menstruation. However, most respondents had poor personal hygiene during menstruation (53,96%). Schools need to provide more references on adolescent reproductive health, especially personal hygiene during menstruation, for school teenagers. Keywords: menstruation; personal hygiene; behavior